Evaluation of Cuban scientific activity within the open science framework: Some reflections - Rúa-Ortiz, Janet; Peralta-González, María Josefa; Gregorio-Chaviano, Orlando; Piedra-Salomón, Yelina (Iberoamerican Journal of Science Measurement and Communication, 2022)
The evaluation of scientific activity has been the object of study by numerous researchers. In Cuba, there are insufficiencies in the forms of monitoring and evaluation of scientific results. Systematizing existing indicators and methodologies to measure scientific-technological activity at the international level, as well as those used in Cuba, is necessary in a context where the use and abuse of indicators proliferate without taking into account elements of judgment that place them in the evaluative context in which they will be used. It is essential to have system indicators that systematically evaluate this activity and temper with the new currents. Considering the context of the application of the indicators, this type of evaluation should be highlighted three fundamental actors in the development of Cuban science and technology: universities, research centers, and high-technology companies. Currently, standardized indicators and reliable and effective policies for evaluating results and impact from the institutional level have not been established sustainably and sustainably. It has been possible to demonstrate that it is possible to use bibliometrics to evaluate scientific activity. However, constructing a methodological solution and a tool applicable to different institutional typologies is still pending, and its results contribute to decision-making.